EVALUASI PUBLIKASI ILMIAH SCIENCEDIRECT BIDANG ENERGI WILAYAH INDONESIA (EVALUATION OF SCIENCEDIRECT PUBLICATIONS IN THE FIELD OF ENERGY AT INDONESIAN TERRITORY) - Himawanto, Himawanto (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2016)
Indonesia until now facing problems in achieving development targets for energy sector because all parties have weak responsibility to invest funds for research growth. Their influence have impact for growth of publications and energy research product which that expensive should proportional with the reputation of scientific media that host it. ScienceDirect is one of it and active as a reputable knowledge media that important to be revealed. So this study aims to evaluate energy research products that published ScienceDirect, mainly from Indonesia zone during 2006-2016. To evaluate, study use bibliometric evaluation to find intensity, ownership designs, and contributor of publications. Results show that news of energy about Indonesia for over decade reached 162 scientific publications and increased as due the research activity growth. Majority of publications disseminated through scientific journals. Its also produced independently and collaborative. Orientation group are dominates and Indonesia capable to coordinate collaboration in its territory. Besides domestic, international collaborative contributed to pulse of energy research in Indonesia and successful level able to offset gains achieved developed countries. A total of 100 essential contributors capable to producing research product more than once and mostly from academics. Participation of domestic researcher looks special among countries on four continents.